Iowa Birdline update, September 3, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Iowa Birdline update for September 3, 1990. Highlights of the update include sightings of a Parasitic Jaeger and Red Knots. Other sightings of note were of Snowy Egrets, Barn Owls, Little Blue Herons, adult and immature Common Moorhens, and 100's of Great Blue Herons and Great Egrets. Also reported were numerous species of shorebirds, waterfowl, Plovers, and Warblers. Epson - sheet feed/flatbed